2010
DOI: 10.4314/ajdas.v8i2.52932
|View full text |Cite
|
Sign up to set email alerts
|

Khat (Catha edulis): academic, health and psychosocial efects on “mature” students

Abstract: The leaves of the plant khat (Catha edulis) are commonly chewed in certain countries of East Africa and the Arabian Peninsula. Chewing of khat leaves has a deep-rooted religious and sociocultural tradition and has a peculiarity of certain influences on the physical, physiological and psychosocial well-being of those involved in the habit of chewing the leaves. The objective of this study was to investigate psychosocial, academic and health implications and reasons for students' involvement in khat chewing habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…Students who had family members and friends engaged in the khat chewing habit were predisposed to the practice of khat chewing. This finding is in line with different studies carried out on substance abuse [ 56 , 72 – 74 ]. The possible reason for the association may be because of social influence and peer pressure that the adult segment of a population has a natural tendency to exercise and reproduce what they have seen in their family and friends.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Students who had family members and friends engaged in the khat chewing habit were predisposed to the practice of khat chewing. This finding is in line with different studies carried out on substance abuse [ 56 , 72 – 74 ]. The possible reason for the association may be because of social influence and peer pressure that the adult segment of a population has a natural tendency to exercise and reproduce what they have seen in their family and friends.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in this meta-analysis we observed that those students who had ever drunk alcohol and ever smoked cigarette were more likely to practice khat chewing as compared to their counterparts. This finding is supported by previous studies conducted in Kenya and Ethiopia[ 74 , 77 ]. These studies reported that history of alcohol consumptions and cigarette smoking were positively associated with khat chewing practice.…”
Section: Discussionsupporting
confidence: 91%
“…It could be speculated that the low prevalence among medical students is due to increased awareness towards the harmful effects of khat. In this study 11.47% of male and 6.72% of females were practiced khat chewing which was higher in males with the large proportion of chewers fall between18-20.Similarly, a study in Jimma university and Harare town 73.5% of chewers and 71.5% of chewers were male respectively (Chanyalew, 2006;Sikiru, 2009). In consistence with this finding, a study done in Addis Ababa revealed 18% of men and 2% of women reported current khat chewing.…”
Section: Discussionsupporting
confidence: 53%
“…Among chewers 51.6% were Muslims; 46.3% of the students reported focus and concentration on their studies as the reason for chewing Khat (Telake, 2007) A cross-sectional community based study done in Jimma University in 2009 on 1200 individuals to evaluate the association between Khat use and mental distress and to determine the prevalence of mental distress and Khat use showed that the Khat use prevalence was found to be 37.8%.Majority of the Khat users were males(73.5%),age group 18-24 (41.1%), Muslims(46.6%), Oromo ethnic group (47.2%), single(51.4%), high school students (46.8%), and employed (80%). (Sikiru, 2009) A cross-sectional study done in Addis Ababa University in June 2009 on 622 undergraduate medical students (year I to internship program) at the school of medicine to determine the prevalence of substance use and identify factors that influenced the behavior showed that in the last 12 months, Khat use was reported by 7% (9% males Vs 1.5% females) of the students. (Tekalign, 2011) A descriptive cross-sectional study done in Harare town, Eastern Ethiopia in April 2010 on 1,890 secondary school students to assess the prevalence and determinants of Khat chewing showed that the overall prevalence of Khat chewing was 24.2%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…see Sykes et al, 2010). Khat is perceived by many to enhance studying capacity and is often used with this intention (Cox and Rampes, 2003;Sykes et al, 2010;Sikiru and Babu, 2009). Similarly, many people outside of the UK chew khat to assist them with their employment performance or to assist in finding employment through social networks (Gebissa, 2008;Hansen, 2010;Teferra et al, 2011).…”
Section: Evidence Of Harms To Individual Usersmentioning
confidence: 99%